The Anguished and the Enchanted "The Little Prince," Revisited - Bowker, M.H (punctum books, 2021)
"In The Anguished and the Enchanted, M.H. Bowker offers a lengthy critical essay and richly annotated English translation of a lost Finnish translation of Antoine de Saint-Exupéry's The Little Prince. Featuring a substantial Translator's Preface, M.H. Bowker develops a psychoanalytic lens through which to regard Saint-Exupéry's classic work, offering a more nuanced and less ""fable-esque"" text than any translation and interpretation to date. On Bowker's reading, dark and primitive unconscious forces - including neglect and abuse at home, the hatred of maturation and development, the projection of feelings of worthlessness onto others, the creation of an absurd and futile world, and more - infest the story, not unlike the Baobab trees dreaded by the little prince. Those already familiar with The Little Prince will find in The Anguished and the Enchanted a new way of regarding what has perhaps become a favorite or even a beloved book. Those unfamiliar with the original work will discover a sometimes tragic, sometimes sympathetic, sometimes harrowing account of the lengths to which persons will go in their struggle to find - or to escape from - meaningful places for themselves in the world of adults."